The Effect of taro tuber (colocasia esculenta L) infusion formulation on reducing cholesterol levels in female mice (mus musculus): Effect of taro tuber (colocasia esculenta L) infusion formulation on reducing cholesterol levels in female mice (mus musculus) - khoiriyah, intan; agni hutahaen, titi; zuhriyah, ainu (Sam Ratulangi University, 2023)
Cholesterol is an essential building material for the body for the synthesis of important substances such as cell membranes and insulating materials around nerve fibers, as well as sex hormones, and kidney children, vitamin D, and bile acids. This study aims to determine which group of phytochemical compounds contained in liquid extract of taro tuber (Colocasia esculenta L.) has activity as a lowering of cholesterol levels and to determine whether taro tuber infusion (Colocasia esculenta L.) can reduce cholesterol levels in female mice. The dose used was the F1 dose of 0.3 ml/30 gram BW/day, the F2 dose was 0.6 ml/30 gram BW/day and the F3 dose was 0.9 ml/30 gram BW/day, in the K+ group using simvastatin 10 mg and K- using aqua injection. The results showed that at a dose of 0.3 ml/30 grams BW/day there was a relatively high reduction in cholesterol levels, namely 61 mg/dL, at a dose of 0.6 ml/30 grams BW/day it decreased by 48.8 mg/dL and at a dose of 0.9 ml /30 gram BW/day decreased with a low average of 19.4 mg/dL. However, a dose of 0.9 ml/30 gram BW/day is the best dose because it can reduce cholesterol levels quickly